Estimation of quantitative levels of diesel exhaust exposure and the health impact in the contemporary Australian mining industry. Issue 4 (15th November 2016) - Peters, Susan; de Klerk, Nicholas; Reid, Alison; Fritschi, Lin; Musk, AW (Bill); Vermeulen, Roel
Abstract : Objectives: To estimate quantitative levels of exposure to diesel exhaust expressed by elemental carbon (EC) in the contemporary mining industry and to describe the excess risk of lung cancer that may result from those levels. Methods: EC exposure has been monitored in Western Australian miners since 2003. Mixed-effects models were used to estimate EC levels for five surface and five underground occupation groups (as a fixed effect) and specific jobs within each group (as a random effect). Further fixed effects included sampling year and duration, and mineral mined. On the basis of published risk functions, we estimated excess lifetime risk of lung cancer mortality for several employment scenarios. Results: Personal EC measurements (n=8614) were available for 146 different jobs at 124 mine sites. The mean estimated EC exposure level for surface occupations in 2011 was 14 µg/m 3 for 12 hour shifts. Levels for underground occupation groups ranged from 18 to 44 µg/m 3 . Underground diesel loader operators had the highest exposed specific job: 59 µg/m 3 . A lifetime career (45 years) as a surface worker or underground miner, experiencing exposure levels as estimated for 2011 (14 and 44 µg/m 3 EC), was associated with 5.5 and 38 extra lung cancer deaths per 1000 males, respectively. Conclusions: EC exposure levels in the contemporary Australian mining industry are still substantial, particularly for underground workers. The estimated excess numbers of lung cancer deaths associated with these exposures support the need for implementation of stringent occupational exposure limits for diesel exhaust.